Verification of the Thermal Expansion Effect of Silicone Molds Intended for Production of the Prototype Components Using Vacuum Casting Technology - Spisak, Peter; Sasik, Robert; Steininger, Jan; Jenis, Jozef (Communications - Scientific Letters of the University of Zilina, 2022)
The article deals with vacuum casting technology and especially with the assessment of the influence of the tempering temperature of silicone molds on the dimensions of future castings. The aim was to evaluate the actual size of the castings, using different tempering temperatures of the molds and different casting materials. After examining the resulting dimensions of the individual castings, a procedure was established by which these effects could be minimized. In the end, a test of the proposed procedure is performed, which confirmed its correctness.
Keywords: tempering; vacuum casting; thermal expansion; silicone mold